Aspects of "Colonization" - Boardman, John (Bulletin of ASOR, 2001)
This paper surveys briefly the rationale and progress of colonizing around the shores of the Mediterranean in the Iron Age. Attention is paid to the evidence for the generally good relations between the Greeks and Phoenicians and the presence of each in the other's settlements. Their spheres of influence mirror closely that of Cypriots and Greeks in the west at the end of the Bronze Age, and some degree of low-level continuity is probable, until demands for land and materials prompted more decisive re-exploration. It was in the second quarter of the eighth century that moves involving serious settlement are most apparent: Euboeans east of Al Mina in Syria (for trade), Euboeans and Phoenicians west to Ischia and Carthage (for land, eventually trade). The phenomena are near-contemporary.